PAI Teacher's Strategy in Overcoming Problems in the Learning Process of the Qur'an and Hadith - Saifullah (Journal of Educational Analytics, 2022)
Teacher's strategy is an effort made by the teacher to achieve learning success. With the right strategy, of course, it will be able to overcome any problems that arise in learning. This study will describe the strategy of the Al-Qur'an Hadith teacher in overcoming problems in the process of learning the Qur'an Hadith at Madrasah Aliyah Negeri (MAN) 2 Central Aceh. This study uses qualitative research, data collection techniques are carried out by observation, interviews and documentation. While the data analysis used was descriptive qualitative analysis. The results showed that in overcoming learning problems at MAN 2 Aceh Tengah, Al-Qur'an Hadith teachers used expository and cooperative learning strategies.